2020
DOI: 10.1098/rspb.2020.0102
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic similarity does not predict necessary sample size for ex situ conservation: a comparison among five genera

Abstract: Effectively conserving biodiversity with limited resources requires scientifically informed and efficient strategies. Guidance is particularly needed on how many living plants are necessary to conserve a threshold level of genetic diversity in ex situ collections. We investigated this question for 11 taxa across five genera. In this first study analysing and optimizing ex situ genetic diversity across multiple genera, we found that the percentage of extant geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 31 publications
6
60
0
1
Order By: Relevance
“…Our results also showed that the collection size should be ≥30 or 50, and this is largely consistent with previous studies (Hoban & Schlarbaum 2014; Hoban et al. 2018, 2020). At each ex situ site, mixing collections from different sources within the nearby region is also an effective approach to increase genetic variation.…”
Section: Discussionsupporting
confidence: 93%
“…Our results also showed that the collection size should be ≥30 or 50, and this is largely consistent with previous studies (Hoban & Schlarbaum 2014; Hoban et al. 2018, 2020). At each ex situ site, mixing collections from different sources within the nearby region is also an effective approach to increase genetic variation.…”
Section: Discussionsupporting
confidence: 93%
“…However, this type of research is only possible if curators of collections consider facilitating future research opportunities as a key objective when introducing plant material to a garden. Consideration should also be given to the sampling design of plant collection trips so that a breadth of genetic material is represented in cultivation (Hoban et al., 2020). This will not only support conservation goals but will also facilitate the evaluation of intraspecific trait variability and help provide focus for plant selection.…”
Section: Discussionmentioning
confidence: 99%
“…Embora nossos valores sejam menores, Franklin (1980) sugere um Ne igual a 50 para conservação a curto e médio prazo para prevenir a perda de alelos raros, enquanto Hoban et al (2020a) recomendam que para reter o potencial adaptativo de espécies e populações um tamanho efetivo populacional maior que 500 é necessário. O número mínimo de 60 matrizes amostradas para propagação por população está de acordo com outros trabalhos que sugeriram número similares, como entre 30-60 para espécies cultiváveis (MARSHALL; BROWN, 1975), 40-80 para espécies virtuais estruturadas em 4 populações como no Jaborandi (HOBAN, 2019), ou entre 30-200 para 11 espécies de 5 gêneros de angiospermas diferentes (HOBAN et al, 2020b). Esse número de matrizes amostradas por população preservaria pelo menos uma cópia de 95% dos alelos de cada população.…”
Section: Discussionunclassified